Transisi Representasi Simbolik-Pictorial dalam Menyelesaikan Masalah Matematika - Fatqurhohman, Fatqurhohman; Susetyo, Agus Milu (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
The purpose of this study is to describe the transition process of symbolic-pictorial representation in solving mathematical problems. Data collection is done by giving written questions which are then followed by structured interviews. The subjects in this study involved seventh grade students who were selected with the consideration that the answers could provide a representations transition process. The results of this study indicate two representations transition processes, namely pictorial to symbolic and symbolic to pictorial. The pictorial-symbolic representation, starting with translating the problem information into the form of an image illustration through the difference in size and number of cakes, integrating the illustrations made through calculations by partitioning them into several equal parts using cutting lines as a modification/simplification process. Symbolic-pictorial representation, shown by finding the key to the problem